Love and Migration: A Simmelian approach - Sabugal, Paulina (Simmel Studies)

(untitled) (Edizioni ETS, 2023)
This text proposes a reflection on relationships of love in today's society from a Simmelian perspective, with a focus on a specific phenomenon: migration for love. Since the 1990s love-motivated migration has emerged in the discussion of the growing importance of social networks and new technologies. Using this social phenomenon that links love and migration as a strating point, the aim is to discuss its relation to some Simmelian concepts such as bonding, cohesion and sociability. This work highlights that migration for love is a typical example of a modern society in which individuals have had to seek new ways to relate and to love, which in turn affect living as a couple and building sentimental projects.